Effect of media compositions on bioprotein production by mixed culture of Phanerochaete chrysosporium and Candida utilis using palm kernel cake and seaweed as substrates - Ilias, Nurul Najihah; Jamal, Parveen; Sulaiman, Sarina; Jaswir, Irwandi; Azmi, Azlin Suhaida; Zainudin , Zaki (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
In aqua-cultural production, feeding represent over 50% of the production cost of which protein constitute the most expensive dietary source. Bioprotein is a promising replacement for the commercial fish feed supplement. In this study, the enrichment of the bioprotein content after solid state fermentation using palm kernel cake and seaweed by the white rot fungus; Phanerochaete chrysoporium and yeast; Candida utilis was investigated. The growth media components were selected from 11 types of media using Plackett-Burman design (PBD) and were optimized by one-factor-at-a-time (OFAT) method with bioprotein concentration (mg/g) as the response. From the screening result using PBD, three media components; K2HPO4, CuSO4.5H2O and MnSO4.H2O were selected for further optimization using OFAT method due to their positive contributions to the response. The final results showed that 5.0 g/L K2HPO4, 3.0 g/L CuSO4.5H2O and 0.1 g/L MnSO4.H2O were found to be the optimum media constituents with 9.0 g/L, MgSO4.7H2O, 0.1 g/L, CaCl2.H2O, 3.0 g/L FeSO4.7H2O and 3.0 g/L peptone as fixed compositions. At this optimum concentration, the protein increment of 11% was observed as compared to the results obtained by using PBD. It was found that mixed cultures can improve the protein concentrations which can be used as fish feed.